ANALYSIS OF FACTORS RELATED TO THE INCIDENCE OF EARLY MARRIAGE IN BOJONGMANIK DISTRICT, LEBAK REGENCY IN 2023 - Nency, Olivia; Oktariani, Venny (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Getting married at the age of less than 18 years is a reality that must be faced by some teenagers throughout the world, including in Indonesia. It is estimated that more than 60 million women aged 20-24 years. Purpose of writing: To find out factors related to the incidence of early marriage in Bojongmanik District, Lebak Regency in 2023. Research Method: This study used a descriptive design with a cross sectional study approach, the sample in this study was 61 people, chi square analysis test. Research Results: There is a relationship between economic status and the incidence of early marriage with a p-value of 0.003<0.05. There is no relationship between parental education and the incidence of early marriage with a p-value of 0.127<0.05. There is no relationship between family history of early marriage and the incidence of early marriage with a p-value of 0.547<0.05. Conclusions and Suggestions: It is hoped that this research can be an input for Bojongmanik District to conduct outreach to the community about the detrimental impact that early marriage can have on health problems. Apart from that, it also provides information on how to prevent early marriage by improving people's economic standard of living.